For Better for Worse Even After Death: Is ‘Widow Politics’ in Ghana’s Fourth Republic Becoming a Reliable Pathway for Women? - Boakye, B.A.P.; Yeboah-Assiamah, E.; Gyekye-Jandoh, M.A. (SAGE, 2022)
The quest to bridge the gender disparity in the politics of Ghana has seen little progress owing to the challenges associated with the passage of the Affirmative Action bill by the actors involved. However, the recent emergence and unconventional adoption of ‘widow succession’ politics in Ghana have sparked some public debates into the viability of the practice in the promotion of women in politics. This paper examined all five identified cases of widow politics in Ghana between 2000 and 2020 (Asutifi South, Shai Osudoku, Ayawaso West Wuogon, Mfantseman and Tempane constituencies) and draws on the widow effect and affirmative action concepts to propose lessons and the possible implication of the practice in Ghana.
Research Articles
Keywords: Widow politics; affirmative action; widow effect; parliament; sympathy vote